A Reanalysis of the Isolated Black Hole Candidate OGLE-2011-BLG-0462/MOA-2011-BLG-191 - Casey Y. Lam; Jessica R. Lu (The Astrophysical Journal, 2023)
There are expected to be ∼10 ^8 isolated black holes (BHs) in the Milky Way. OGLE-2011-BLG-0462/MOA-2011-BLG-191 (OB110462) is the only such BH with a mass measurement to date. However, its mass is disputed: Lam et al. measured a lower mass of 1.6–4.4 M _⊙ , while Sahu et al. and Mróz et al. measured a higher mass of 5.8–8.7 M _⊙ . We reanalyze OB110462, including new data from the Hubble Space Telescope (HST) and rereduced Optical Gravitational Lensing Experiment (OGLE) photometry. We also rereduce and reanalyze the HST data set with newly available software. We find significantly different (∼1 mas) HST astrometry than Lam et al. in the unmagnified epochs due to the amount of positional bias induced by a bright star ∼0.″4 from OB110462. After modeling the updated photometric and astrometric data sets, we find the lens of OB110462 is a ${6.0}_{-1.0}^{+1.2}{M}_{\odot }$ BH. Future observations with the Nancy Grace Roman Space Telescope, which will have an astrometric precision comparable or better to HST but a field of view 100× larger, will be able to measure hundreds of isolated BH masses via microlensing. This will enable the measurement of the BH mass distribution and improve understanding of massive stellar evolution and BH formation channels.